Assessment of cardiac autonomic functions by heart rate variability in patients with restless leg syndrome - Abdülmelik Yıldız; Cennet Yıldız; Ahmet Karakurt (KARE Publishing, 2018)
Objective: The aim of the present study was to investigate cardiac autonomic effects in restless leg syndrome (RLS) using heart rate variability (HRV). Methods: A total of 35 patients with RLS and 35 healthy individuals were enrolled in the study. The severity of RLS symptoms was assessed using the International Restless Legs Syndrome Study Group rating scale (IRLS). The correlation between the severity of RLS symptoms and HRV parameters measured on an electrocardiogram was analyzed. Results: There were no statistically significant differences between the 2 groups with respect to age, gender, or body mass index. The mean heart rate was 85+-7.1 bpm in the RLS group compared with 79.6+-5.5 bpm in the control group (p=0.001). The standard deviation (SD) of all normal to normal (NN) intervals (SDNN), the mean of the deviation of 5-minute NN intervals over the entire recording (SDNN index), and the SD of the average NN intervals calculated over a 5-minute period of the entire recording (SDANN) were significantly lower in the RLS group compared with the control group (p<0.05 for all). There were no statistically significant differences between the 2 groups in the square root of the mean squared differences of successive NN intervals (RMSSD) and the proportion of adjacent RR intervals differing by >50 milliseconds in the 24-hour recording (pNN50) values (p=0.119 and p=0.07, respectively). In patients with RLS, the low frequency (LF) power and LF/high frequency (HF) ratio were significantly higher than those in the control group (2248.6+-245.6 vs 712.1+-346.3, 10.7+-3.7 vs 2.9+-1.8; p<0.0001 and p<0.0001, respectively). Compared with the control group, the RLS group had lower values for HF power, but the difference was not statistically significant (p=0.07). The severity of RLS symptoms was negatively correlated with the SDNN, SDANN index, and pNN50 (r=-0.453 and p=0.009, r=-0.340 and p=0.046, r=-0.446 and p=0.007, respectively), and positively correlated with LF power (r=0.681 and p<0.0001). Conclusion: The study data demonstrated that cardiac autonomic impairment is associated with RLS.